A manufacturing method of integrated ceramic heat spreaders embedded with interconnected microchannels. (15th October 2019) - Tian, Bohan; Yang, Deming; Ma, Hongbin; Xu, Jiujun; Liang, Dalong
Abstract: In this study, a fabrication method is developed to manufacture an integrated alumina heat spreader embedded with an oscillating heat pipe (OHP). This novel manufacturing process simplifies the fabrication of the microchannels inside the ceramic and provides a new method for the fabrication of integrated ceramic heat dissipation devices. The fabrication method includes the use of a wax core, die pressing, isostatic pressing and the sintering process. The fabrication process developed herein can effectively prevent cracking and achieve a hermetically sealed interconnected microchannel in the substrate. In addition, this paper presents an analysis of the internal channel formation mechanism and illustrate the major factors related to the fabrication process. SEM was used to characterize the microstructure of the sintered alumina, and X-ray diffraction (XRD) was conducted for phase analysis. The thermal performance of the OHP was also investigated. The results showed that the oscillation motion was intense and the thermal resistance was greatly reduced to 0.3 K/W at 52 W. Compared to a plain alumina plate, the thermal performance of the integrated alumina heat spreader can be improved by 97%. Graphical abstract: Unlabelled Image Highlights: A fabrication method was developed to manufacture an alumina heat spreader embedded with an oscillating heat pipe (OHP). A hermetically sealed interconnected microchannel with six turns can be fabricated in the substrate. The spinel phase (MgAl2 O4 ) and the binder content (polyvinyl alcohol) had a strong impact on crack prevention. The thermal resistance of the heat spreader achieved 0.3 K/W at high load.